The Effects of Automation and Role Allocation on Team Performance. (November 2019) - Dikmen, Murat; Li, Yeti; Farrell, Philip; Ho, Geoffrey; Cao, Shi; Burns, Catherine
An experiment was conducted to investigate the effects of automation and role allocation on performance in a simulated picture compilation task with fourteen two-person student teams. In the absence of automation support, the system integrated sensor information. In the presence of automation support, the system both integrated sensor information and identified contacts. Roles were assigned either based on warfare domain or geographical sectors. Results showed that human-automation system performance was similar in two automation conditions, but participants were slower in classifying tracks and overall classified fewer tracks when the automation was present. We conclude that working with automation may lead to degraded team performance due to complacency and additional task complexity.